Peran Brand Trust dalam Memediasi Dampak Brand Image, Electronic Word of Mouth, dan Influencer terhadap Purchase Desicion Sunscreen Facetology - Nayla Salsabila Putri Arshinta; Piji Pakarti; Ariati Anomsari; Tito Aditya Perdana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study analyzes the role of brand trust in mediating the influence of brand image, electronic word of mouth, and influencer on the purchase decision of Facetology products in Semarang. Using a quantitative approach, this study involved 149 Facetology consumers as respondents selected through purposive sampling. The results showed that brand image, electronic word of mouth, and influencer had a positive and significant effect on brand trust and purchase decision. Brand trust was also proven to have a positive and significant effect on purchase decision with the strongest influence compared to other variables. In addition, brand trust effectively mediated the relationship between the third independent variable on purchase decision. This study reveals Facetology's success in addressing the "comedogenic" issue through clarification based on scientific evidence, which strengthens brand image and builds consumer trust. These findings emphasize the importance of building and maintaining brand trust as a strategic asset in the beauty industry, especially in the digital era with a variety of product choices and information sources available.